ACOUSTIC RECONSTRUCTION AND DIGITAL SIMULATION OPPORTUNITIES IN MAQAM PERFORMANCE - Nizomova Mohinur Ulug‘Bek Qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the potential of acoustic reconstruction and digital simulation in maqam performance. The study examines how traditional maqom sounds can be analyzed, digitally modeled, and reproduced with high fidelity, preserving microtonal nuances, timbral characteristics, and modal structures. Acoustic measurements, spectral analysis, and computational techniques are applied to simulate performance scenarios, enabling both educational and research applications. The findings highlight the integration of historical performance practices with modern technology, offering tools for musicians, educators, and researchers to study, reconstruct, and innovate within the field of maqom music.